PERANCANGAN APLIKASI PENJUALAN FASHION DAN AKSESORIS BERBASIS WEB PADA TOKO FITRIN - Nur Sa'adah, Fitria; Voutama, Apriade (JATI (Jurnal Mahasiswa Teknik Informatika), 2023)
Nowadays, online sales are increasingly popular among the public, and in response to this trend, many stores have started to expand their business by creating web-based sales applications. The use of web-based sales applications has become a dominant trend in the trading industry. In this journal, research was conducted with the aim of designing a web-based sales application planning specifically for Toko Fitrin. This research uses data collection methods through observations, interviews, and literature studies to understand user needs and preferences. Toko Fitrin is a fashion and accessories store located in the city of Karawang. This application is designed using PHP programming language and utilizing MySQL database. The main features of this application include product search and product ordering. The test results show that this application runs smoothly and without significant obstacles. Functional testing using the Blackbox testing method resulted in 100% conformity between the design model and the system that has been built. The research findings show that a web-based sales application for Fitrin's store has the potential to increase store efficiency and productivity, as well as provide a better purchasing experience for customers. Therefore, this application is expected to be a valuable alternative to develop Fitrin's store business.